2002
DOI: 10.1017/s0959269502000340
|View full text |Cite
|
Sign up to set email alerts
|

La production du E caduc facultatif est-elle prévisible? Un début de réponse

Abstract: Dans cette étude, nous examinons les facteurs qui influencent la production des mots comportant un E caduc facultatif en syllabe initiale. Nous avons demandé à des locuteurs francophones de raconter quatre histoires comportant des mots où le E caduc est facultatif, et nous avons ensuite calculé, pour chaque mot, un taux de production avec effacement. Afin de prédire les taux obtenus, sept facteurs ont été choisis et, pour chacun d'eux, un coefficient de corrélation a été calculé. Une combinaison des trois fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
10

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 5 publications
1
20
0
10
Order By: Relevance
“…According to the dominant pronunciation, the letter e is not pronounced although it is written (e.g., Content et al, 1990;Delattre, 1966;Dufour, Peereman, Pallier, & Radeau, 2002;New et al, 2004). Concerning internal schwas, Racine and Grosjean (2002) argued that the pronunciation of the silent e in French is obligatory (e.g., atelier, /atəlje/), optional (e.g., cheval, / əval/ or / val/), or forbidden (e.g., avenir, /avni /). For our third set, all the words with an internal schwa belonged to the last category.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the dominant pronunciation, the letter e is not pronounced although it is written (e.g., Content et al, 1990;Delattre, 1966;Dufour, Peereman, Pallier, & Radeau, 2002;New et al, 2004). Concerning internal schwas, Racine and Grosjean (2002) argued that the pronunciation of the silent e in French is obligatory (e.g., atelier, /atəlje/), optional (e.g., cheval, / əval/ or / val/), or forbidden (e.g., avenir, /avni /). For our third set, all the words with an internal schwa belonged to the last category.…”
Section: Methodsmentioning
confidence: 99%
“…Each pair was composed of a control word and a schwa word. All the schwa words contained an internal silent e, not pronounced in French (Racine & Grosjean, 2002). Both control and schwa words had an obstruent-liquid intervocalic consonant cluster including a plosive or fricative consonant (p, b, v, t, d) followed by a liquid one (l, r).…”
Section: Methodsmentioning
confidence: 99%
“…Many examples have been discussed in literature, including English vowel reduction (Bybee, 2001), English t/d deletion (Bybee, 2000;Coetzee, 2009aCoetzee, , 2009bPhillips, 2006), French schwa deletion (Fougeron & Steriade, 1997;Racine & Grosjean, 2002), and so forth. Lexical frequency plays an important role in these phonological processes.…”
Section: Variation In Phonologymentioning
confidence: 99%
“…Hooper (1976) Similar results have been found in other languages as well. Racine & Grosjean (2002) investigated schwa deletion in Swiss French by asking native speakers to tell four stories with words that have optional schwa deletion. To predict the rate of schwa deletion, they calculated the correlation coefficients of seven factors, including lexical frequency, the frequencies of the variants (the token frequencies of lexical items that undergo schwa deletion and those do not), consonant context (the consonants preceding and following the schwa), force of articulation (the co-articulatory effects of consonants preceding and following the schwa), the deletion rate of the preceding word, articulation rate, and discursive rate (the rate of speech deviated from the topics of the stories).…”
Section: Lexical Frequencymentioning
confidence: 99%
“…The relative frequencies of the pronunciation variants of these words were obtained by means of a rating experiment, as previous investigations have shown that speakers are able to correctly rate the frequencies of phonological variants. For instance, Racine and Grosjean (2002) showed that the frequencies of the two pronunciation variants for schwa words estimated by a group of 18 speakers predicted the variants' frequencies in the productions of 16 different speakers.The pictures for the words were taken from multiple sources: two from Alario and Ferrand (1999), 50 from the Google picture database (http://www.google.fr), and 12 pictures were drawn specifically for this experiment. Many of the pictures we used were thus not extracted from a psycholinguistic database, and we had no information on their "name agreement" values.…”
mentioning
confidence: 99%